Triclosan-Selected Host-Associated Microbiota Perform Xenobiotic Biotransformations in Larval Zebrafish. (5th September 2019) - Weitekamp, Chelsea A; Phelps, Drake; Swank, Adam; McCord, James; Sobus, Jon R; Catron, Tara; Keely, Scott; Brinkman, Nichole; Zurlinden, Todd; Wheaton, Emily; Strynar, Mark; McQueen, Charlene; et al.
Abstract: Microbiota regulate important physiologic processes during early host development. They also biotransform xenobiotics and serve as key intermediaries for chemical exposure. Antimicrobial agents in the environment may disrupt these complex interactions and alter key metabolic functions provided by host-associated microbiota. To examine the role of microbiota in xenobiotic metabolism, we exposed zebrafish larvae to the antimicrobial agent triclosan. Conventionally colonized (CC), microbe-free axenic (AX), or axenic colonized on day 1 (AC1) zebrafish were exposed to 0.16–0.30 µM triclosan or vehicle on days 1, 6, 7, 8, and 9 days post fertilization (dpf). After 6 and 10 dpf, host-associated microbial community structure and putative function were assessed by 16S rRNA gene sequencing. At 10 dpf, triclosan exposure selected for bacterial taxa, including Rheinheimera . Triclosan-selected microbes were predicted to be enriched in pathways related to mechanisms of antibiotic resistance, sulfonation, oxidative stress, and drug metabolism. Furthermore, at 10 dpf, colonized zebrafish contained 2.5–3 times more triclosan relative to AX larvae. Nontargeted chemical analysis revealed that, relative to AX larvae, both cohorts of colonized larvae showed elevations in 23 chemical features, including parent triclosan and putative triclosan sulfate. Taken together, these data suggest that triclosan exposure selects for microbes that harbor the capacity to biotransform triclosan into chemical metabolites with unknown toxicity profiles. More broadly, these data support the concept that microbiota modify the toxicokinetics of xenobiotic exposure.